Los retos de las ciudades del Perú frente al cambio climático. Aproximaciones desde la Justicia Ambiental - Ortiz Sánchez, Iván (2022)
Faced with the urgent call to action raised in the latest IPCC report, this paper takes a panoramic review at the general problems of Peruvian cities tackling climate change, revealing that the challenge is twofold: to build resilience to climatic variability, but above all to overcome the structural causes that produce high levels of social and ecological vulnerability. It is concluded that the four dimensions of environmental justice -distribution, recognition, participation, capacities- allow a more complete analysis of the vulnerabilities to overcome and achieve fair resilience; also, progresses have been found in this regard.